Percepções existenciais: Liberdade, trabalho e felicidade nas aulas e currículo de Filosofia do Estado de São Paulo - Gabriel, Fabiane Malvestiti [UNIFESP] (2019)
The studies that I proposed in this dissertation aim to analyze the current intermittency of the discipline of Philosophy in the curriculum of the State of São Paulo, verifying if it is in fact a propagator of certain ideals of socioemotional or affective and social competences of the adolescent, mainly in the moral aspect in the school environment. Thus, this dissertation has as a main objective to make a qualitative field research through round table conversations and semi-structured interviews or video interviews, seeking to bring into light how students become involved with learning situations on the themes of freedom and happiness which are presented to them during Philosophy classes, analyzing and considering the relevance of such knowledge on their decision-making skills in the labor market, in an existential and psychosomatic sphere.In this way, a field research was carried out using the consulted and studied theoretical reference as a basis, with students from the 3rd grade of High School (last year of the 12 years required by the State) and their philosophy teachers, as well as testimonies (on video), in which the participants were able to expose their perspectives and desires within their current existential situation.